Is Silver Diamine Fluoride Really a Magic Alternative in Pediatric Caries Management? : An Advanced Clinical Approach - Singhania, Shreepriya; Bhojraj, Nandlal; Shanbhog, Raghavendra (Recent Developments in Medicine and Medical Research Vol. 10, 2021)
Aim and Objective: To review the success of silver diamine fluoride (SDF) in the management of caries in children. Background: The current caries management strategy is based on a biological model. Children with early childhood caries require behaviour management as well as effective and thorough caries management, for which an algorithm-based approach is proposed.Silver diamine fluoride functions as a tertiary preventive procedure, reducing the negative consequences of established disease (cavity) and restoring, thus improving the child's quality of life. It's a magic bullet that combines silver's antibacterial properties with highly concentrated fluoride's remineralizing properties. Review Results: Previous systematic reviews found that SDF was effective in halting caries in primary teeth and root caries in adults. Because caries removal is not required, SDF application is appropriate when other caries management modalities are unavailable or impractical. Aside from the arrested lesion turning black, no significant complication of SDF use in children was reported. Conclusion: Despite the unappealing black staining, a significant number of parents chose SDF over advanced pharmacological behaviour management techniques, and it is truly the magical alternative in children as it supports the contemporary "biological approach" to caries management. Clinical Significance: During the COVID-19 pandemic, SDF allows the interruption of aerosol-generating procedures and serves as an interim treatment procedure to arrest dentin caries and prevent the development of pulpitis, which requires further intervention with an aerotor. Most importantly, theSDF application is child-friendly and provides exceptional success rates when used where indicated.